Congenital hepatic cyst with intracystic hemorrhage: Two rare cases reports in the Chinese Han population. Issue 42 (October 2016) - Ni, Qingqiang; Zhang, Minfeng; Yang, Cheng; Cai, Wenchang; Zhao, Qian; Shen, Weifeng; Yang, Jiamei
Abstract: Introduction: Fast-growing congenital hepatic cysts with intracystic hemorrhage are rare in clinical practice. Additionally, the clinical manifestations of and laboratory and imaging findings for this condition are often nonspecific and are particularly difficult to differentiate from those of hepatobiliary cystadenoma and cystadenocarcinoma, thus posing great challenges for diagnosis and treatment. The 2 case reports presented here aim to analyze the diagnosis and treatment of 2 rare cases of congenital hepatic cysts with intracystic hemorrhage in the Chinese Han population to provide an important reference for the clinical diagnosis and treatment of this condition. Diagnoses: These 2 case reports present 2 rare cases of congenital hepatic cysts with intracystic hemorrhage. Case 1 involved a 31-year-old patient with a very large, fast-growing hepatic cyst with intracystic hemorrhage and elevated carbohydrate antigen 199. Case 2 involved a patient with intense, paroxysmal right upper abdominal pain; computed tomography suggested a hepatic cyst with intracystic hemorrhage and possibly hepatobiliary cystadenoma. Outcomes: Both patients underwent liver resection. Postoperative follow-up showed that for both patients, the symptoms improved, the laboratory findings returned to normal levels, and the surgical outcomes were satisfactory. Conclusion: Liver resection is an ideal treatment for patients with congenital hepatic cysts with intracystic hemorrhage, and especially those with fast-growing, symptomatic hepatic cysts or hepatic cysts that are difficult to differentiate from hepatobiliary cystadenoma and cystadenocarcinoma.